The Study of Social Affecting Factors on Adolescent’s Social Happiness Covered by the Imam Khomeini Relief Committee in Pole Dokhtar City - eshagh arjmand; daryoush rezapour; Khadijeh Hasanpour Afrineh (توسعه اجتماعی, 2019)
Joy in life, happiness, mutual trust and commitment are in the same group which show the attitude of individuals towards self and world. The main purpose of the research is to study of influential factors on the rate of social joy between juvenile of the Imam Khomeini s Committee in the city of Pole Dokhtar together the data, we have used survey method as well as a structured questionnaire. Using Cochran Formula, we selected 219 people as a sample from the population (506). Findings showed that there is a significant relationship between the feeling of anomie, feeling of relative deprivation, income, social trust, religiosity and social happiness. Besides, the results of the multi regression analysis of social happiness showed that income, relative deprivation and social trust could explain. Variance of social happiness is (R²=0/449).